Karakteristik Kewirausahaan, Lingkungan Bisnis dan Kapabilitas Organisasi: Pengaruhnya terhadap Strategi Bisnis dan Kinerja Usaha (Kajian pada Koperasi di Sulawesi Tenggara) - Adnan Hakim (Jurnal Aplikasi Manajemen, 2010)
The objectives of this research are to determinate how the manager entrepreneurship effect organization capability. business strategy, business performance; Investigate how External business environment effect organization capability, business strategy, business performance; Determinate influence of organizational capability on business strategy and business performance, and measure the effect of business strategy on business performance. This study used cooperative as unit of analysis and manager as respondent. Data for the study were collected  from 119 cooperatives and 119 managers covered as respondents. The result indicate that, Business performance is largely determined by The Manager entrepreneurship, Organization capability, Business strategy and External business environment through Organization capability and Business strategy. Further, it was shown that, the organization capability and Business strategy are strong intervening variable in supporting the relation between External business environment and Business performance. In addition Organization capability was weak intervening variable in supporting the relation between The Manager entrepreneurship and Business performance.